A metal–organic framework-derived pseudocapacitive titanium oxide/carbon core/shell heterostructure for high performance potassium ion hybrid capacitors. Issue 32 (4th August 2020) - Li, Hongxia; Chen, Jiangtao; Zhang, Li; Wang, Kunjie; Zhang, Xu; Yang, Bingjun; Liu, Lingyang; Liu, Weisheng; Yan, Xingbin
Abstract : A high performance potassium-ion hybrid capacitor is constructed by coupling a MOF-derived pseudocapacitive TiO2 /C@NPSC heterostructure anode with a MOF-derived activated carbon cathode. Abstract : For the emerging potassium-ion energy storage technology, the major challenge is seeking suitable electrode materials with a robust structure and fast kinetics for the reversible insertion/desertion of potassium ions. Here, a pseudocapacitive core–shell heterostructure of titanium oxide/carbon confined into N, P, and S co-doped carbon (TiO2 /C@NPSC) is obtained by pyrolyzing a metal–organic framework (MOF) precursor of MIL-125 (Ti) modified by poly(cyclotriphosphazene- co -4, 4′-sulfonyldiphenol) polymer. The distinctive structure of TiO2 /C@NPSC can effectively buffer the volume variation of TiO2 nano-grains during the charge/discharge process, increase the electron/charge transfer, provide abundant active sites, and boost the pseudocapacitive-dominated K + -storage. Consequently, the TiO2 /C@NPSC anode displays superior cyclability and fast kinetics behavior. Upon integrating it with a high capacitance activated carbon cathode derived from another MOF precursor, the as-built potassium-ion hybrid capacitor achieves a high-energy density of 114 W h kg −1 and a power output of 21 kW kg −1 . Moreover, in a wide working potential window of 0–4.2 V, the device also maintains over 91.6% of its initial capacity after 10 000 cycles, showing a superior cycle stability. Our results are conducive to understanding the importance of anode-engineering for designing advanced PIHCs.